Epigenetics of Fear, Anxiety and Stress – Focus on Histone Modifications - Ell, Marco A.; Schiele, Miriam A.; Iovino, Nicola; Domschke, Katharina (Current Neuropharmacology, 2024)
Fear-, anxiety- and stress-related disorders are among the most frequent mental disorders. Given substantial rates of insufficient treatment response and often a chronic course, a better understanding of the pathomechanisms of fear-, anxiety- and stress-related disorders is urgently warranted. Epigenetic mechanisms such as histone modifications - positioned at the interface between the biological and the environmental level in the complex pathogenesis of mental disorders - might be highly informative in this context. The current state of knowledge on histone modifications, chromatin-related pharmacology and animal models modified for genes involved in the histone-related epigenetic machinery will be reviewed with respect to fear-, anxiety- and stress-related states. Relevant studies, published until 30th June 2022, were identified using a multi-step systematic literature search of the Pub- Med and Web of Science databases. Animal studies point towards histone modifications (e.g., H3K4me3, H3K9me1/2/3, H3K27me2/3, H3K9ac, H3K14ac and H4K5ac) to be dynamically and mostly brain region-, task- and time-dependently altered on a genome-wide level or gene-specifically (e.g., Bdnf) in models of fear conditioning, retrieval and extinction, acute and (sub-)chronic stress. Singular and underpowered studies on histone modifications in human fear-, anxiety- or stress-related phenotypes are currently restricted to the phenotype of PTSD. Provided consistent validation in human phenotypes, epigenetic biomarkers might ultimately inform indicated preventive interventions as well as personalized treatment approaches, and could inspire future innovative pharmacological treatment options targeting the epigenetic machinery improving treatment response in fear-, anxiety- and stressrelated disorders.
Keywords: chromatin